2020
DOI: 10.1038/s41598-020-73434-0
|View full text |Cite
|
Sign up to set email alerts
|

The recurrence rate of ovarian endometrioma in women aged 40–49 years and impact of hormonal treatment after conservative surgery

Abstract: The aim of this study was to evaluate the rate of and risk factors for recurrence ovarian endometrioma after conservative surgery in patients aged 40–49 years. This retrospective, single-center study included 408 women between January 2008 and November 2018. All patients underwent ovarian cyst enucleation, were pathologically diagnosed with ovarian endometrioma and were followed up for ≥ 6 months. Recurrence was defined as a cystic mass with diameter ≥ 2 cm detected by sonography. Recurrence rate after conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In the present study, GnRH-a was administered for 3-6 months after surgery. We found that postoperative GnRH-a treatment did not signi cantly reduce the recurrence rate of endometrioma, which is consistent with those of previous studies [27,28], Muzii reported that preoperative administration of GnRH-a for three months did not signi cantly reduce the postoperative recurrence rate of ovarian endometrioma [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, GnRH-a was administered for 3-6 months after surgery. We found that postoperative GnRH-a treatment did not signi cantly reduce the recurrence rate of endometrioma, which is consistent with those of previous studies [27,28], Muzii reported that preoperative administration of GnRH-a for three months did not signi cantly reduce the postoperative recurrence rate of ovarian endometrioma [29].…”
Section: Discussionsupporting
confidence: 92%
“…This nding is also consistent with those of previous studies [3,6]. However, in a multivariate analysis of women aged 40-49 years, ovarian endometrioma larger than 5.5 cm was the only risk factor for postoperative recurrence [27]. The ndings of some previous studies suggest that cyst size is a risk factor for recurrence of the disease [14,20].…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the average recurrence rate of EM in 2 years is about 20% ( 0–89.6%), and the recurrence rate in 5 years is as high as 50% (15.1–56%) [ 12 ]. Lee et al [ 13 ] reported that the cumulative recurrence rates of 1 year, 2 years, 2.5 years and 5 years after ovarian endometrioma surgery are 3.7%, 6.7%, 11.1%, 16.7%, respectively. In the follow-up of patients with ovarian endometriotic cyst after surgery, Xiao-Yan Li et al [ 14 ] found that the cumulative incidence of recurrence in 5–10 years after surgery was 15.4%, 16.8%, 19.3%, 22.5%, 22.5%, 22.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although drugs have shown good therapeutic effects, the following points should be considered when using them. First, high levels of estrogen induce potential side effects [ 13 ]. Second, the recurrence rate remains high.…”
Section: Introductionmentioning
confidence: 99%